2020
DOI: 10.1097/j.pain.0000000000002035
|View full text |Cite
|
Sign up to set email alerts
|

High-dose spinal cord stimulation for patients with failed back surgery syndrome: a multicenter effectiveness and prediction study

Abstract: The use of high-dose spinal cord stimulation (HD-SCS) has increased drastically during the past few years, with positive results. However, there remains a deficit of real-world data of the effectiveness of HD-SCS. Therefore, the primary aim was to evaluate the effectiveness of HD-SCS in patients with failed back surgery syndrome (FBSS). The second aim was to develop a prediction model for a holistic responder. One hundred ninety-four patients were recruited to a multicenter real-world registry. Self-reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 40 publications
1
52
0
Order By: Relevance
“…Previous research already revealed that achieving functional goals is more important to patient satisfaction than obtaining reduction in self-reported pain [ 25 ]. Rather recently, the focus has shifted towards functioning instead of only focusing on pain relief, with multidimensional outcome measures such as holistic responders [ 26 ] or composite scores [ 27 ]. Another important issue in light of the ongoing opioid epidemic is the reduction in medication use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research already revealed that achieving functional goals is more important to patient satisfaction than obtaining reduction in self-reported pain [ 25 ]. Rather recently, the focus has shifted towards functioning instead of only focusing on pain relief, with multidimensional outcome measures such as holistic responders [ 26 ] or composite scores [ 27 ]. Another important issue in light of the ongoing opioid epidemic is the reduction in medication use.…”
Section: Discussionmentioning
confidence: 99%
“…“High density in spinal cord stimulation: virtual expert registry” (10) investigated the effectiveness, safety, and feasibility of HD‐SCS in a population of FBSS with chronic back and leg pain. In this registry, the investigated study population consisted of neurostimulation‐naĂŻve “new patients” (11) and “rescue patients,” the latter defined as patients in whom the initial effectiveness of conventional SCS is lost over time (12). The aim of the current study was to investigate the impact of HD‐SCS on pain medication use, not only on opioid use, but also on other types of pain medication, measured by the Medication Quantification Scale III (MQS).…”
Section: Introductionmentioning
confidence: 99%
“…Highdensity or high-dose SCS, in which longer pulse widths and/or higher frequencies are used, has also shown clinical utility. [11][12][13][14] Beyond just programming parameter changes, devices that target novel anatomical structures, such as the dorsal root ganglion, have been approved by regulatory bodies all over the world. 15,16 Multiple detailed reviews have been published on putative mechanisms of action specific to these various approaches.…”
Section: Introductionmentioning
confidence: 99%